Perceived Stress Related to Open Distance Learning (ODL) Among Undergraduate University Students in Malaysia - Ilma Fariha Zaharulail; Aina Amanina Abdul Jalil; Nor Safwan Hadi Nor Afendi (Asian Journal of Medicine & Health Sciences, 2023)
In response to the coronavirus disease 2019 (COVID-19) crisis, the World Health Organisation (WHO) declared COVID-19 a pandemic on March 11, 2020. This pandemic has affected everyone in many ways and students are among those who suffered the most during the quarantine period. While being socially isolated, students may experience tension, stress, irritation, and discontent. Students are frequently worried and overwhelmed as a result of too many homework submissions, interminable quizzes, conflicting deadlines, and online assessments. A cross-sectional survey was performed using a self-administered anonymous online Perceived Stress Scale (PSS) questionnaire. The questionnaire was distributed to undergraduate university students in Malaysia, and the data was analysed using descriptive statistics and the Chi-square Test. Out of 405 respondents, the perceived level of stress was seen higher among males (46.67%) students studying in IPTA (67.41%), third year (37.78%), and students from the STEM program (51.11%).Most university students in Malaysia had moderate stress levels during open and distance learning (ODL). There was also a significant association between the level of stress in students during ODL and sociodemographic factors such as place of study, gender, and year of study.